SOFTWARE ANALYSIS IN THE FIELD OF GEODESY - Hunko, I. (Municipal economy of cities. Series: «Economy science», 2022)
In connection with the development of modern geodetic technologies, there is a need to quickly and efficiently perform automated processing of source data. Today, the market for surveying software is diverse and is divided into common products and specialized software packages. Geodetic works are not possible without the use of geographic information technologies and software. Therefore, the purpose of this article is a detailed analysis of the software packages used in Ukraine, as well as an analysis of their capabilities, accessibility, clarity and additional functions in the field of geodesy. Geodetic works belong to the tasks of geoinformation analysis, and with the help of modern electronic geodetic equipment increases the accuracy of work, the processing of which is carried out by computer-aided design (CAD). After analyzing the functionality of software products, we can conclude that most of them are not fully functioning automated products of full-scale systems. An important factor when choosing a software package is the ability to use for free or the low cost of a license to use. But, in addition to cost, when choosing a product, considerable attention is paid to the complexity of implementation and operation of such CAD. Among the most famous representatives that have proven themselves in Ukraine, we can highlight such packages as CREDO III, Digitals, and software packages created on the CAD platform. In general, such programs are set up by companies that have direct links with Western firms to facilitate data resolution. Other products can only be used to solve specific tasks of a narrower direction. When choosing a software, it is important that the program meets the objectives and processes all types of topographic and geodetic works. The application and implementation of new software packages in the field of geodesy provides greater accuracy and quality of topographic and geodetic works. When choosing software, many Ukrainian business leaders, as experience shows, focus on CREDO III, Digitals and CAD software packages to be able to work in a single information space at different stages of project development.